Carers' Assessment, Skills and Information Sharing: Theoretical Framework and Trial Protocol for a Randomised Controlled Trial Evaluating the Efficacy of a Complex Intervention for Carers of Inpatients with Anorexia Nervosa. (10th September 2012) - Goddard, Elizabeth; Raenker, Simone; Macdonald, Pamela; Todd, Gillian; Beecham, Jennifer; Naumann, Ulrike; Bonin, Eva‐Maria; Schmidt, Ulrike; Landau, Sabine; Treasure, Janet
Abstract Experienced Carers Helping Others (ECHO) is a guided self‐help intervention for carers of people with eating disorders to reduce distress and ameliorate interpersonal maintaining factors to improve patient outcomes. The aim of this paper is to describe the theoretical background and protocol of a randomised controlled trial that will establish whether ECHO has a significant beneficial effect for carers and the person they care for. Individuals with anorexia nervosa and carers will be recruited from eating disorder inpatient/day patient hospital services in the UK. Primary outcomes are time until relapse post‐discharge (patient) and distress (carer) at 12 months post‐discharge. Secondary outcomes are body mass index, eating disorder symptoms, psychosocial measures and health economic data for patients and carers. Carers will be randomised (stratified by site and illness severity) to receive ECHO (in addition to treatment as usual) or treatment as usual only. Potential difficulties in participant recruitment and delivery of the intervention are discussed. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.